The Recovery-Adaptation Paradox: A Review Comparing Cold Water Immersion and Hot Water Immersion on Immediate Recovery vs. Long-Term Muscular Adaptations - Brankowska, Karolina; Dziegciarczyk, Anna; Wiater, Zuzanna Ewa; Włodarczyk, Aleksandra; Swoboda, Kamil; Jakubowska, Marta; Olejnik, Michał; Górka, Piotr Artur; Domagała, Szymon; Kądziołka, Witold Jerzy (Journal of Education, Health and Sport, 2026)
Background. Cold water immersion (CWI) has long been the gold standard for post-exercise recovery, primarily due to its potent analgesic effects and perceived reduction in muscle soreness. However, recent molecular and longitudinal evidence suggests that CWI may fundamentally interfere with the adaptive processes following resistance exercise. In contrast, hot water immersion (HWI) is emerging as an alternative that may support recovery without compromising hypertrophy or explosive power. Objectives. This review synthesizes current evidence regarding the molecular, vascular, and functional responses to thermal interventions, specifically contrasting the “regeneration paradox” of CWI with the facilitative mechanisms of HWI. The objective is to determine which immersion strategy optimizes the balance between acute recovery, characterized by the alleviation of muscle soreness (DOMS) and restoration of performance, and long-term hypertrophic gains. By synthesizing current evidence, this work intends to provide a clearer framework for athletes and recreational trainees in choosing recovery modalities that do not compromise chronic training outcomes. Methods. A synthesis of recent meta-analyses, systematic reviews and experimental trials was conducted, focusing on myogenic signaling, ribosome biogenesis, vascular kinetics, and long-term performance outcomes. Findings. Included in the full text of the abstract provided in the manuscript. Conclusion. This review addresses the “Recovery-Adaptation Paradox” by highlighting that the optimal immersion strategy is strictly objective-dependent. While CWI effectively optimizes acute recovery through analgesia and masking fatigue, it may compromise long-term hypertrophic gains and explosive power by disrupting anabolic signaling. In contrast HWI provides a strategic alternative for athletes prioritizing chronic training outcomes, as it facilitates restoration without interfering with the muscle’s endogenous adaptive pathways.